2017
DOI: 10.1002/cssc.201700589
|View full text |Cite
|
Sign up to set email alerts
|

Gliding Arc Plasmatron: Providing an Alternative Method for Carbon Dioxide Conversion

Abstract: Low-temperature plasmas are gaining a lot of interest for environmental and energy applications. A large research field in these applications is the conversion of CO into chemicals and fuels. Since CO is a very stable molecule, a key performance indicator for the research on plasma-based CO conversion is the energy efficiency. Until now, the energy efficiency in atmospheric plasma reactors is quite low, and therefore we employ here a novel type of plasma reactor, the gliding arc plasmatron (GAP). This paper pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
183
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(202 citation statements)
references
References 77 publications
6
183
3
Order By: Relevance
“…The energy efficiency was calculated for the best conditions (CO 2 :diluent gas = 1:2). It was reported that the energy efficiency of DBD plasma is lesser than gliding arc and microwave plasma system [29]. The curve indicates decreasing energy efficiency with increasing discharge power, which is in agreement with earlier observations [24,27].…”
Section: Optical Emission Spectra (Oes)supporting
confidence: 91%
See 2 more Smart Citations
“…The energy efficiency was calculated for the best conditions (CO 2 :diluent gas = 1:2). It was reported that the energy efficiency of DBD plasma is lesser than gliding arc and microwave plasma system [29]. The curve indicates decreasing energy efficiency with increasing discharge power, which is in agreement with earlier observations [24,27].…”
Section: Optical Emission Spectra (Oes)supporting
confidence: 91%
“…CO2 splitting may be initiated by the electron impact excitation from lowest vibrational level to highest vibrational level followed by vibrational-vibrational collision [29,30]. The …”
Section: Optical Emission Spectra (Oes)mentioning
confidence: 99%
See 1 more Smart Citation
“…[9] Ah igh voltage was applied to the GAP by means of ad irect current power source. This yielded ar eactor volume of 3.82 cm 3 .T he setup can be used with different anode diameters, but the present configuration yielded the most pronounced reverse vortex flow,a sr evealed by computational fluid dynamics simulations, and provided the best CO 2 conversion and energy efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] Nonthermal plasma (NTP) approach has been used as an alternative to thermocatalytic methods. Various NTP systems such as corona discharges, [18] atmospheric plasma jet, [19] gliding arcs, [20][21][22] glow discharge, [23] and dielectric barrier discharges (DBDs) [24][25][26] have been tested for DRM and CO 2 mitigation. Among all, DBD attracted more attention due to the uniform distribution of microdischarges, presence of high energetic electrons, capability of initiating the reaction under ambient conditions, etc.…”
Section: Introductionmentioning
confidence: 99%